Factors that Influence the Value of Infrastructure Companies Listed on The Indonesian Stock Exchange - Faisal, Yusuf; Bandiyono, Agus (Akuntansi: Jurnal Akuntansi Integratif, 2024)
This study aims to determine the effect of dividend policy, capital structure, profiitability and leverage on firm value. This research uses quantitave data, the sample in this study is infrastructure sector companies which are listed on Indonesia Stock Exchange in the period 2017-2022 as many as 14 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 Software. The results of this study indicate that the dividend policy variabel has a positive and statistically insignificant effect on firm value, the capital structure variabel has a positive and statistically insignificat effect on firm value, the profitability has a positive and statistically signifinact and the leverage variabel has a positive and statistically insignificant on firm value. This study focuses on firm value, where this study focuses on infrastructure sector companies.